A web-based scoping review assessing the influence of smoking and smoking cessation on antidiabetic drug meabolism: implications for medication efficacy - Bellanca, Carlo Maria; Augello, Egle; Di Benedetto, Giulia; Burgaletto, Chiara; Cantone, Anna Flavia; Cantarella, Giuseppina; Bernardini, Renato; Polosa, Riccardo; , the DiaSmokeFree Working Group; Di Ciaula, Agostino; Dugal, Tabinda; Kengne, Andre; et al. (Frontiers in Pharmacology, 2024)
Currently 1.3 billion individuals globally engage in smoking, leading to significant morbidity and mortality, particularly among diabetic patients. There is urgent need for a better understanding of how smoking influences antidiabetic treatment efficacy. The review underscores the role of cigarette smoke, particularly polycyclic aromatic hydrocarbons (PAHs), in modulating the metabolic pathways of antidiabetic drugs, primarily through the induction of cytochrome P450 (CYP450) enzymes and uridine diphosphate (UDP)-glucuronosyltransferases (UGTs), thus impacting drug pharmacokinetics and therapeutic outcomes. Furthermore, the review addresses the relatively uncharted territory of how smoking cessation influences diabetes treatment, noting that cessation can lead to significant changes in drug metabolism, necessitating dosage adjustments. Special attention is given to the interaction between smoking cessation aids and antidiabetic medications, a critical area for patient safety and effective diabetes management. This scoping review aims to provide healthcare professionals with the knowledge to better support diabetic patients who smoke or are attempting to quit, ensuring tailored and effective treatment strategies. It also identifies gaps in current research, advocating for more studies to fill these voids, thereby enhancing patient care and treatment outcomes for this at-risk population.